Polyarteritis nodosa is an unforeseen borderline paradoxical adverse reaction in a female patient with rheumatoid arthritis treated with tofacitinib - Yu. V. Muraviev; S. G. Radenska-Lopovok; V. V. Lebedeva; S. Yu. Alamankina (Современная ревматология)
The paper describes the occurrence of polyarteritis nodosa in a patient with rheumatoid arthritis during treatment with tofacitinib. It considers the reasons why this condition should be regarded as an unforeseen borderline paradoxical adverse reaction.